The Effect of Parents' Social Support and Self-Efficacy on Students' Happiness at Islamic Boarding School - Khozran, Dzikriani; Suud, Fitriah M. (Intiqad: Jurnal Agama dan Pendidikan Islam, 2025)
This study aims to determine the effect of parental social support and self-efficacy on students' happiness and the extent of each variable's contribution. With a quantitative approach and correlational method, 110 students of Daarul Fikri Integrated Islamic Boarding School Senior High School became respondents through total sampling and filling out a Likert scale questionnaire. The regression analysis results showed that parental social support significantly affected students' happiness (β = 0.130; p = 0.001), while self-efficacy did not have a significant effect partially (β = 0.053; p = 0.367). Simultaneously, both variables had a significant effect (F = 6.855; p = 0.002) with R² = 0.115, meaning that this model can explain 11.5% of happiness. The implication of this research is that parental social support has a significant and positive influence on the happiness of students. However, students' self-efficacy does not have a significant partial effect on their happiness.